Are multinational enterprises in retreat?. Issue 2 (16th July 2018) - Vahlne, Jan-Erik; Ivarsson, Inge; Alvstam, Claes G.
Abstract : Purpose: This paper aims to contribute to the debate concerning the asserted end of the globalization process. Design/methodology/approach: This paper is a description of the evolution of all Swedish MNEs, the 50 largest companies and the ten truly global MNEs, building on data compiled by the authors, mainly from annual reports. Findings: The largest Swedish MNEs have continued to globalize and have at the same time improved their financial performance during the period of study, 2010-2016. Practical implications: The proposition that multinationals are heading home cannot be confirmed in the Swedish case. There is therefore a need to compare Swedish experiences with other national examples to better generalize the findings. Social implications: The political decisions regarding external trade and foreign direct investment should support continuous liberalization and facilitation of cross-border economic interaction. Originality/value: As Swedish MNEs are more globalized than the average in advanced economies, this study offers insight into the contemporary internationalization process.